HTTP blocking in MM: facebook.com, instagram.com, signal.org, telegram.org, twitter.com +2 more (Myanmar) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Myanmar. Data sourced from CensoredPlanet.
Censorship Incident ID: MM-2026-0006. Severity: warning. Confidence: 85%